Al-Madinah al-Fadilah in Islamic Political Philosophy: Exploration of al-Farabi's Thought - Muhammad Iqbal Oki Akbar; Muhamad Fajar Pramono (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study analyzes Islamic political philosophy in al-Farabi's thought. This research is a literature research that uses descriptive analysis methods and qualitative analysis. Al-Farabi put forward the concept of al-Madinah al-Fadilah to reconcile faith and reason. The concept of government in al-Farabi's theory is based on the leadership style and tradition of Prophet Muhammad (PBUH), an apostle and caliph. In addition, in this theory the concept of good character is influenced by the ideas of Plato and Aristotle, especially the idea that views humans as social beings. Al-Farabi was also heavily influenced by the social and political movements of the Abbasid period, political conflicts, riots, political stability, and insecurity were the main causes of this idea. The principles embodied in almost all forms of intellectuals born outside the Islamic world show great differences with Greek philosophy, especially in addressing the challenges of the times, to God and the world These influences show that Islamic thought is different from other forms of thought.